From Clinical Diagnosis to the Discovery of Multigene Rare Sequence Variants in Pseudoxanthoma elasticum: A Case Report - Lofaro, Francesco Demetrio; Mucciolo, Dario Pasquale; Murro, Vittoria; Pavese, Laura; Quaglino, Daniela; Boraldi, Federica (Frontiers in Medicine, 2021)
Pseudoxanthoma elasticum (PXE) is a rare autosomal recessive disease clinically characterized by early cutaneous alterations, and by later clinically relevant ocular, and cardiovascular manifestations. ABCC6 genetic tests are used to confirm clinical PXE diagnosis, but this strategy may be rather challenging when only one ABCC6 pathogenic variant is found. A next-generation sequencing approach focusing on 362 genes related to the calcification process and/or to inherited retinal diseases was performed on a patient with clinical PXE diagnosis (skin papules and laxity, angioid streaks and atrophy) who was carrier of only one ABCC6 rare sequence variant. Beside ABCC6, several rare sequence variants were detected which can contribute either to the occurrence of calcification (GGCX and SERPINF1 genes) and/or to ophthalmological manifestations (ABCA4, AGBL5, CLUAP1 and KCNV2 genes). This wide-spectrum analysis approach facilitates the identification of rare variants possibly involved in PXE, thus avoiding invasive skin biopsy as well as expensive and time-consuming diagnostic odyssey and allows to broaden and to deepen the knowledge on this complex rare disease and to improve patients’ counselling, also with a future perspective of personalized medicine.